Illicit market for tobacco and alcohol in Ukraine: method of statistical evaluation (World of finance, 2019)
Introduction. Illegal trade in alcoholic beverages / tobacco products deprives the state of tax revenues and increases the availability of such excisable goods around the world, undermining the goals of social policy. In this regard, the most urgent issue is the introduction and implementation of effective control strategies for the circulation of such goods based on the assessment of their illegal circulation. Accordingly, the urgent issue is the development of a methodology for assessing such illegal circulation and its use in the practice of fiscal authorities, it will allow obtaining information on the volume of non-receipt of excise tax and the effectiveness of controls on illegal circulation. Proceeding from the peculiarities of the development of the alcohol and tobacco segments of the excisable goods market in Ukraine, the authors of the article have developed and proposed a Methodology for assessing the illegal circulation of such excisable goods, it involves the use of macro methods, in particular, the method for estimating the implementation and method of estimating tax revenue losses. The source data base of the Methodology was provided by the official statistics of the State Statistics Service of Ukraine, the United Nations Trade Commerce Statistics Database, WHO data and the Second Global Adult Tobacco Survey.The purpose of the article is a development of methodology for statistical estimation of the volumes and share of illicit market for tobacco and alcohol and tax gap from such treatment.Results. The proposed methodology consists of four stages, which provide for the determination of the volume of consumption of alcoholic beverages / tobacco products and their sales in the retail chain; trade gap and adjusting the volume of sales of cigarettes in the retail chain; volumes and shares of illegal circulation; the tax break and its share in total tax revenues. Conclusionof the evaluation of the illegal circulation of alcoholic beverages and tobacco products according to the Methodology is indicate about the significant part of them from the legal market of such excisable goods, which was made up 36% for alcoholic beverages on average for 2012–2016, and for tobacco products in the scenario, adjustment of sales volume for trade the gap was 19,3%, in the scenario without adjustment was 13,1%. In turn, the share of losses of excise tax and VAT receipts from illegal circulation of alcoholic beverages / tobacco products was 4,8% in total tax revenues during the analyzed period in the first scenario and in the second scenario was 4,4%.